DIGITALIZATION OPPORTUNITIES AND CHALLENGES IN THE BANKING SYSTEM OF UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the process of digitalizing the banking system in Uzbekistan, its opportunities, and the challenges that arise. The study examines the technological, economic, and social aspects of digitalizing banking services, as well as their impact on customers and banking operations. The results show that the expansion of internet and mobile banking services enables faster bank operations, improves service quality, and promotes financial inclusion. At the same time, regional infrastructure disparities, insufficient professional qualifications, customers’ low digital literacy, and cybersecurity issues have been identified as factors limiting the digitalization process. As a scientific novelty, the study proposes an indicator called the “digital trust index,” which evaluates the level of digitalization of banking services together with customer trust. Based on this, the article develops practical recommendations for improving and enhancing the effectiveness of digital banking services.